Quasi-Parametric Chirped-Pulse Amplification Simultaneously Enables High Peak Power and High Average Power - Zhe Yin; Jingui Ma; Jing Wang; Peng Yuan; Guoqiang Xie; Liejia Qian (IEEE Photonics Journal, 2019)
Ultrafast lasers with both high peak-power and high average-power will open new avenues for many applications. While conventional technologies of Ti:sapphire laser amplification and optical parametric amplification can achieve several tens of watts of average-power, scaling to a higher average-power is challenging due to thermal limitations. Here, we demonstrate that the quasi-parametric chirped-pulse amplification (QPCPA) can break this average-power barrier. QPCPA is proven robust against the thermal dephasing by obstructing the back-conversion effect. Numerical simulations show that QPCPA based on a Sm:YCOB crystal can support peak powers of 3 TW at 5 kHz and 13.5 PW at 1 Hz, with average powers exceeding 150 W in both cases. We also discuss the prospects of QPCPA with the recently proposed configuration of temperature-insensitive phase matching, which is promising to simultaneously achieve higher peak-power and higher average-power.